EBV-Derived miR-BART20-3p Influences Proliferation and Migration in EBV-Positive Gastric Cancer Models by Suppressing PPARα - Qiong Wu; Guiying Ye; Xiazhen Xu; Xianchang Zeng; Biyun Wu; Fan Xin; Lu Zhang; Xu Lin; Xinjian Lin; Wannan Chen (Microorganisms)
Epstein–Barr virus (EBV) is the first oncogenic DNA virus known to encode microRNAs (miRNAs) and has been implicated in the pathogenesis of multiple malignancies, including a distinct subset of gastric cancers (EBV-associated gastric cancer, EBVaGC). However, the functional roles of individual EBV-encoded miRNAs in EBVaGC remain poorly defined. In this study, we integrate bioinformatic and experimental analyses to uncover a novel oncogenic axis driven by EBV-encoded miR-BART20-3p. Analysis of public transcriptomic datasets revealed that peroxisome proliferator-activated receptor α (PPARα) is significantly downregulated in EBVaGC compared with EBV-negative gastric tumors. We confirmed that both PPARα mRNA and protein are reduced in EBVaGC cell lines and primary tumor specimens, and that this reduction inversely correlates with miR-BART20-3p levels. A dual-luciferase reporter assay demonstrated that miR-BART20-3p directly binds the PPARα 3′-UTR. Functionally, miR-BART20-3p overexpression in AGS cells enhanced proliferation and migration, whereas inhibition of miR-BART20-3p in EBV-infected AGS cells attenuated these phenotypes. Mechanistic studies employing PPARα-specific siRNA together with qRT-PCR and ELISA reveal that suppression of PPARα or overexpression of miR-BART20-3p leads to upregulation of interleukin 6 (IL-6), indicating disruption of the PPARα–IL-6 regulatory axis. Collectively, EBV-encoded miR-BART20-3p promotes EBVaGC progression by directly targeting PPARα, and thereby derepressing IL-6 expression. This miRNA–PPARα–IL-6 pathway may serve as both a mechanistic biomarker and a novel therapeutic target in EBVaGC.